The Effect of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Capital Structure on Firm Value with Profitability as an Intervening Variable in Banking Companies - Dea Mutiara Otoxsusilo; Christina Sri Ratnaningsih; Irany Windhyastiti; Umu Khouroh; Irany Windhyastiti (University of Merdeka Malang, 2023)
This study aims to test and analyze the effect of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and Capital Structure on Firm Value with intervening variable Profitability. The sample used is six (6) banking companies that are included in the First Movers on Sustainable Banking category initiated by the Financial Services Authority (OJK) and the World Wide Fund for Nature (WWF-Indonesia) and meet other predetermined criteria. The analysis method uses the path analysis method. The results of this study indicate that GCG and CSR variables have a significant negative effect on profitability, while the capital structure has a significant positive effect on profitability. Another finding of this study is that GCG and profitability have an insignificant positive effect on firm value, while CSR and capital structure have a significant positive effect on firm value. In addition, this study also found that profitability cannot mediate GCG, CSR, and capital structure on firm value.Capital Structure, Corporate Social Responsibility, Firm Value, Good Corporate Governance, Profitability